HUBUNGAN METODE MENGAJAR DOSEN TERHADAP HASIL BELAJAR MATAKULIAH ALJABAR STKIP PARIS BARANTAI KOTABARU (Studi Kasus) - Mukhsin Mukhsin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2014)
ABSTRACTThe background of this study is that the method of teaching faculty in almost every college has a similar method. On the other hand, most students consider learning mathematics is a difficult subject and the impact on learning outcomes in mathematics, especially algebra course. One of the factors that affect student learning outcomes is a method of teaching faculty. The purpose of this study was (1) to determine learning outcomes algebra course STKIP Paris Barantai. (2) to find a significant relationship between methods of teaching faculty on learning outcomes of the course algebra STKIP Paris Barantai. This study uses a quantitative correlation method, meaning that the researchers collected data by conducting a field survey and then searched the relationship between variables. The sampling technique in this study using simple random sampling. The sample in this study were taken 70% of each class. With a total population of 89 students, so that the sample in this study were 59 students. Collecting data using questionnaires to collect data variable X, while in Y using a data acquisition list of the final value (DPNA) students. Questionnaire instruments before use to obtain objective data, first testing the validity and reliability. Hypothesis testing showed that there was a positive correlation between the methods of teaching faculty to student results, indicated by the Pearson product moment correlation of 0,257 at significance level Î± = 0,05 was obtained t count equal to 2,015 and t table of 2,002.Â Key word: Faculty teaching methods, learning outcomes, Algebra.